Improving Students’ Motivation to Learn English by Serving English Book with Local Wisdom - Ismiyani, Nining (Jurnal Pendidikan Indonesia, 2021)
In improving English language skills, reading serves as a supportive activity. Reading is fundamental to improve students’ vocabulary in order to facilitate their speaking and writing skills. However, one of the barriers that students face in reading contents obtained from overseas references is the level of reading difficulty which is classified as quite high that it reduces reading motivation. This study aims to develop an English reading comprehension book that contains the local values to motivate students in learning English as well as an as attempt to preserve local culture among millennial students who have massively been exposed to western lifestyles. This study used a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. However, only the initial three stages out of five will be discussed. 187 participants studying at a university in West Kalimantan were invited online to take part in the needs analysis stage and initial evaluation. The research resulted in a book with an ISBN in accordance to the participants’ needs and points of view in the analysis stage. Initial evaluation reveals that the book is interesting and easier to read that it is expected to increase motivation of English learners.